2021
DOI: 10.3390/foods10123115
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on the Impact of Cattle Handling on Post-Mortem Myofibrillar Muscle Proteome and Meat Tenderization

Abstract: This study investigated the effect of different cattle management strategies at farm (Intensive vs. Extensive) and during transport and lairage (mixing vs. non-mixing with unfamiliar animals) on the myofibrillar subproteome of Longissimus thoracis et lumborum (LTL) muscle of “Asturiana de los Valles” yearling bulls. It further aimed to study the relationships with beef quality traits including pH, color, and tenderness evaluated by Warner–Bratzler shear force (WBSF). Thus, comparative proteomics of the myofibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 75 publications
(163 reference statements)
0
6
0
Order By: Relevance
“…Regarding the pairwise comparison between FL and PH cattle, similarities in animal performance and carcass traits were reported by Gómez et al [ 7 ], so comparing these treatments may allow for a better understanding of the broad differences between pasture and feedlot feeding systems. Many studies have reported the differences in performance and meat quality of cattle finished in different production systems, grass or grain, including changes in muscle fiber type composition, intramuscular fat accumulation, meat tenderness, and color [ 1 , 2 , 4 , 5 , 6 , 35 ]. However, the molecular mechanism and pathways responsible for differences between grass and grain-fed animals are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pairwise comparison between FL and PH cattle, similarities in animal performance and carcass traits were reported by Gómez et al [ 7 ], so comparing these treatments may allow for a better understanding of the broad differences between pasture and feedlot feeding systems. Many studies have reported the differences in performance and meat quality of cattle finished in different production systems, grass or grain, including changes in muscle fiber type composition, intramuscular fat accumulation, meat tenderness, and color [ 1 , 2 , 4 , 5 , 6 , 35 ]. However, the molecular mechanism and pathways responsible for differences between grass and grain-fed animals are still largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found a positive correlation between pork LD Warner-Bratzler shear force and myosin light chains 1 and 2 abundance at 3 d postmortem ( Lametsch et al, 2003 ). Subsequent LC–MS/MS experiments with myofibrillar protein fractions have found troponin-T ( Liu et al, 2021 ), myosin binding protein C, myosin light chain 1/3, and myosin regulatory light chain 2 ( Sierra et al, 2021 ) to be differentially abundant based on quality or grouping in pork and beef. Two main explanations account for the observed variations in thick and thin filament proteins across groupings.…”
Section: Resultsmentioning
confidence: 99%
“…A higher degree of MLC2 break down was found in beef aged with the M. flavus biostarter. According to Picard et al [ 44 ], Sierra et al [ 45 ], and Ding et al [ 46 ], the degree of degradation of those proteins (MLC2) is one of the indicators associated with the beef myofibrillar proteins’ effective proteolysis, particularly related to the tenderness of meat.…”
Section: Discussionmentioning
confidence: 99%